Detachment. «Teacher». Indifference/disaffection of the educator - García Lozano, Francisco José (Razón y fe, 2018)
It is a film as uncomfortable as the existence of a lot teachers in these days. The situation narrated in the film is the dissaffectiion which is born not from the professional incompetence, but from the commercialization and the trivialization which the western world’s teaching has become.
Keywords: disaffection; teaching; teacher; shool faiture